A review of game-based learning in fuel cell education for secondary students / Nur Fadhilah Abdul Jalil ... [et al.] - Abdul Jalil, Nur Fadhilah; Hasran, Umi Azmah; Mat Noor, Siti Fadzilah; Norman, Muhammad Helmi (Universiti Teknologi MARA, 2024)
The need for fuel cell education is now critical since fuel cell exposure can build future economies, human capital, and environmental consciousness, as fuel cell is the future green technology. This can be communicated through educational programs that guarantee the transfer of knowledge is relevant and transparent. This paper provides an overview of the need to prepare our students, who will be the next generation of potential fuel cell users and designers, for the impending widespread adoption and use of hydrogen fuel cell technology. To ensure that the learning process is interesting and inspiring, mobile games are demonstrating their promise as useful instruments for assisting fuel cell teaching. With the application of various game design elements, gamebased learning has been demonstrated to boost cognitive growth, learning experiences, learning engagement, and motivation. As a result, research must continue to focus on the creation of fuel cell education modules for secondary students that use mobile games as learning tools. By integrating game-based learning into fuel cell education, we can inspire and empower the next generation of professionals to drive the transition towards sustainable energy future.